The role of psychological contract breach and leader-member exchange quality in Machiavellianism and organisational cynicism - Wu, Hao; Subramaniam, Anusuiya; Rahamat, Syafiqah (Emerald Publishing, 2024)
Purpose: Based on the trait activation theory and social exchange theory, this study proposed a model of the impact of Machiavellian personality on organisational cynicism (OC) through the mediating effect of psychological contract breach (PCB) and the moderating role of leader-member exchange (LMX) quality in PCB and OC. Design/methodology/approach: A three-time points survey involving 264 employees from China’s hotel industry was conducted using quantitative methods. Subsequently, a structural equation model was constructed. Findings: The results revealed that Machiavellianism positively affects OC, and PCB plays a mediating role in this process. In addition, LMX quality can buffer the effect of the PCB on OC. Practical implications: The study’s findings provide another insight into the relationship between Machiavellianism, PCB and OC. Managers must pay attention to the control of PCB and the establishment of LMX quality. Originality/value: The study significantly contributes to hotel literature, as the Machiavellian personality subject has not been adequately investigated in the field to date. © 2024, Emerald Publishing Limited.